2021
DOI: 10.1111/anu.13319
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded dietary lipid levels on growth, feed utilization, body composition and metabolism in juvenile white leg shrimp, Penaeus vannamei (Boone, 1931) reared in inland saline water of 10 g/L salinity

Abstract: A feeding trial was performed for 60 days to determine the dietary lipid requirement of Penaeus vannamei juveniles reared in inland saline water (ISW) of 10 g/L salinity. Six iso-nitrogenous (360 g/kg crude protein) and heterocaloric (15.4-17.6 KJ DE/g) semipurified diets were prepared with graded level of lipid viz., 20, 40, 60, 80, 100 and 120 g/kg (L2-L12 with 20 g/kg incremental level). Two hundred and seventy P. vannamei juveniles (5.51 ± 0.01 g) were randomly allocated (15 shrimps/200 L) into six treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Additionally, previous findings show that dietary lipid levels are crucial for growth in low-salinity environments (Jannathulla et al, 2019; Chuphal et al, 2021). The current study showed that diets made through extrusion have higher lipid and energy content.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, previous findings show that dietary lipid levels are crucial for growth in low-salinity environments (Jannathulla et al, 2019; Chuphal et al, 2021). The current study showed that diets made through extrusion have higher lipid and energy content.…”
Section: Discussionmentioning
confidence: 95%
“…Many studies have shown that the whole-body lipid content increases with increasing dietary lipid levels and excess lipids in the diet may lead to excess fat deposits in the tissues [ 3 , 22 , 33 ]. In this study, the crude lipid content of crayfish did not show significant differences among all the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most crucial consideration is an adequate nutritional information, especially the knowledge of the dietary nutrient requirements of species in relation to age and environmental conditions [ 3 ]. Dietary lipid is one of the crucial nutrients after protein to spare protein for energy supply, and thus contributes an important role in optimizing the dietary protein for the growth of living organisms [ 4 ]. Dietary lipid also plays an important role in providing essential fatty acids, phospholipid, and fat-soluble vitamins to fish [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, excess dietary lipid levels beyond the optimum level can cause abdominal fat deposition and fatty liver syndrome due to increased leptin levels [ 10 ], which affects the general wellbeing of the fish and the characteristic muscle quality [ 11 ]. So, lipid must be included in the fish diet at an optimum level to maximize protein utilization for better growth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation